Navigating Political Ecotourism through Quadruple Helix Collaboration: The Case of Lake Sebedang during Covid-19 Pandemic - Zhan, Fuzy Firda; Seli, Seli; Sahrul, Sahrul (PT. Riset Press International, 2025)
Sebedang Lake is one of the mainstay natural tourist attractions of West Kalimantan Province, located between Sempalai Sebedang Village and Sepuk Tanjung Village, Sebawi District, Sambas Regency. When the Covid-19 pandemic caused world tourism activity to decline, Lake Sebedang continued operating with high tourist numbers. This research analyzed the quadruple helix collaboration on the development of Lake Sebedang ecotourism during the Covid-19 pandemic from a political ecotourism perspective. The method used in this research is descriptive qualitative, with data sourced from interviews and literature studies. The research results found that the success of Lake Sebedang in maintaining optimal tourism activities during the Covid-19 pandemic could not be separated from the quadruple helix collaboration, namely government, academicians, business, and community. Through this collaboration, a Covid-19 volunteer post and guard team are available, health protocols are implemented by checking temperatures, as well as providing hand washing equipment at the entrance to Sebedang Lake, and visitors are required to wear masks, including at cafes in the Sebedang Lake area by the Circular Letter of the Indonesian Minister of Trade Number 12 of 2020 concerning Restoration of Activities Carried Out During the Covid-19 and New Normal Period.